PARTISIPASI ORANGTUA DALAM PELATIHAN BAHASA INGGRIS ANAK-ANAK SANGGAR ANGKRINGAN BOCAH SINAU - wardhani, m kusuma (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2023)
Sanggar Angkringan Bocah Sinau in Yogyakarta, which consists of elementary school children in grades 4-6, has been running for 6 years. This non-formal learning activity served by internship students is intended for children who are economically disadvantaged, but have a high enthusiasm for learning. But the pandemic put a halt to all these activities. Problems arise, parents are anxious because children's education is not monitored, do not have more funds for education, and interns who usually teach, return to their respective areas. This need, fulfilled by community service programs, is carried out for 1 year with educational counseling activities for parents and English language training for children. The method of implementing the program starts from: discussion with sanggar caretaker; site visits; determine the appropriate solution of activities; arrange the schedule; implementation of activities; evaluation and follow-up. Activities during June 2022 to May 2023, include 3 counseling sessions for parents, as well as 12 English language training for children, which are carried out online. The results of this activities ; parents are happy and enthusiastic about participating in the program without the need to spend money, parents learn how to accompany and motivate children to learn English with various media, children experience a significant improvement in English language skills. Parents hope that in the future there will also be an English lesson program for parents. Key Words : training , English, sanggar